The Role of Islamic Financial Institutions in the Development of MSMEs: An Analysis of Financing and Mentoring for Islamic-Based Micro-Enterprises in West Java - Diana Setiawati; Nayla Putri Aryani; Mozart Tiasylva Syah Nuhandika; Arifkha Gita Zahara; Berliana Azizah; Kanaya Ayodya Indra Prasta; Indah Ayu Dewi Maharani (Takaza Innovatix Labs Ltd., 2025)
MSMEs play a vital role in the Indonesian economy, yet they still face challenges in accessing financing and managing their businesses. Islamic Financial Institutions (IFIs) offer a financing alternative that is not only based on the principles of fairness and profit-sharing, but also prioritizes social sustainability and Sharia compliance. This study aims to analyze the selection and feasibility assessment mechanisms of micro-enterprises implemented by these institutions, as well as to examine the financing and mentoring models implemented to support MSME sustainability. The research method employed a qualitative approach through library research with content analysis of various literature sources related to Islamic financing and MSME empowerment. The results indicate that these institutions implement a selection mechanism based on the Sharia-compliant 5C concept, encompassing character, capacity, capital, business conditions, and collateral, with an emphasis on moral aspects and Sharia compliance. The financing models used include mudharabah, musyarakah, murabahah, ijarah, and qardhul hasan, combined with business mentoring such as management training, Islamic business ethics development, and field monitoring. This integrated approach has been proven to improve financial discipline, business sustainability, and social benefits for MSMEs. Thus, LKS functions not only as a capital provider but also as an agent for empowering the community's economy based on the principles of maqasid sharia.